Hepatitis C virus molecular evolution: Transmission, disease progression and antiviral therapy - Victoria Preciado, Maria; Valva, Pamela; Escobar-Gutierrez, Alejandro; Rahal, Paula [UNESP]; Ruiz-Tovar, Karina; Yamasaki, Lilian [UNESP]; Vazquez-Chacon, Carlos; Martinez-Guarneros, Armando; Carlos Carpio-Pedroza, Juan; Fonseca-Coronado, Salvador; Cruz-Rivera, Mayra (Baishideng Publishing Group Inc, 2014)
Hepatitis C virus (HCV) infection represents an important public health problem worldwide. Reduction of HCV morbidity and mortality is a current challenge owned to several viral and host factors. Virus molecular evolution plays an important role in HCV transmission, disease progression and therapy outcome. The high degree of genetic heterogeneity characteristic of HCV is a key element for the rapid adaptation of the intrahost viral population to different selection pressures (e.g., host immune responses and antiviral therapy). HCV molecular evolution is shaped by different mechanisms including a high mutation rate, genetic bottlenecks, genetic drift, recombination, temporal variations and compartmentalization. These evolutionary processes constantly rearrange the composition of the HCV intrahost population in a staging manner. Remarkable advances in the understanding of the molecular mechanism controlling HCV replication have facilitated the development of a plethora of direct-acting antiviral agents against HCV. As a result, superior sustained viral responses have been attained. The rapidly evolving field of anti-HCV therapy is expected to broad its landscape even further with newer, more potent antivirals, bringing us one step closer to the interferon-free era. (C) 2014 Baishideng Publishing Group Inc. All rights reserved.
Keywords: Hepatitis C virus; Evolution; Phylogenetics; Drug resistance; Clinical outcome